PENGARUH PROPORSI TAPIOKA DAN TERIGU TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK BERSELEDRI - Kusuma, Theodora Dessryna; Suseno, Thomas Indarto Putut; Surjoseputro, Sutarjo (Widya Mandala Surabaya Catholic University, 2013)
Crackers is a popular food in Indonesia. Currently developing the cracker is a cracker without protein in the addition of vegetable materials (vegetable crackers). The addition of celery in cracker can be used as a diversification effort. Crackers are generally made from tapioca that affect the quality of crackers. A good quality appearance is translusent and compact. Substitution of wheat flour is expecte d to improve the quality of the resulting crackers. This research aims to study the influence of the proportion of tapioca and wheat flour in celery crackers characterstics and to determine the proportion of tapioca and wheat flour crackers that can produce good quality and acceptable in terms of sensory. The main materials used in this study is tapioca, wheat flour, fresh celery, baking powder, and water. Research methods with Random Design Group a single factor, namely the proportion of tapioca and wheat. Level of treatment consist of eight levels, proportion wheat flour 0, 5, 10, 15, 20, 25, 30, 35% with three replications. Proportion in the manufacture of tapioca and wheat flour crackers real influence on the water content, volume expantion, bulk density after fried crackers, color, and hardness. Increasing of wheat flour make water content, bulk density, redness, yellowness, and hardness increase too, but volume expantion and lightness decrease. The use of tapioca and wheat flour in addition to the crackers do not give the real effect on the bulk density crackers after drying. The selection of the best treatment based on the weighting test, including volume expantion and organoleptic (appearance, crispness, flavor, and color), the best treatment is proportion wheat flour 15%.